Psychometric assessment of individual differences in second language reading anxiety for identifying struggling students in classrooms - Hamada, Akira; Takaki, Shuichi (Frontiers in Psychology, 2022)
Assessing learners’ individual differences helps identify students who need teacher support in classrooms. Previous studies have examined second language (L2) achievement based on reading anxiety because reading is an input-based activity essential for successful L2 learning. This study applied a latent rank model to identify L2 learners who are likely to be struggling or successful in classrooms according to their L2 reading anxiety symptoms. Moreover, a psychometric function was developed to determine the cutoff anxiety scores that discriminate against their substantial differences. The model was applied to responses from the Foreign Language Reading Anxiety Scale (FLRAS) provided by 335 Japanese learners of English. The results showed that the FLRAS classified students into three ranked groups with ordinal information regarding L2 reading anxiety. Rank 1 exhibited good conditions in L2 reading anxiety. Rank 2 reported high anxiety toward unfamiliar grammar during L2 reading. Rank 3 had even higher anxiety levels especially for vocabulary and grammatical knowledge deficits and reading difficulty. The cutoff anxiety scores estimated by the model detected students who failed their L2 class with 79% accuracy. Theoretical, methodological, and pedagogical issues in language anxiety were discussed in terms of diagnosis and different approaches to teaching L2 reading.